Metformin and Biliary Tract Cancer in Patients With Type 2 Diabetes - Tseng, Chin-Hsiao (Frontiers in Oncology, 2020)
Aim: This retrospective cohort study evaluated whether metformin use in patients with type 2 diabetes mellitus might reduce the risk of biliary tract cancer (BTC); and explored whether metformin use might affect the overall survival in patients who developed BTC. Methods: New-onset type 2 diabetes patients aged 25-75 years during 1999-2005 were enrolled from the Taiwan’s National Health Insurance and followed up until December 31, 2011. A total of 287,995 ever users and 16,229 never users were identified (unmatched original cohort) and a 1:1 matched pairs of 16,229 ever users and 16,229 never users based on propensity score (PS) were created (matched cohort). Hazard ratios were estimated by three Cox regression models: 1) adjusted for PS; 2) incorporated with the inverse probability of treatment weighting using PS; and 3) all covariates treated as independent variables. Overall survival was compared between ever users and never users of metformin who developed BTC. Results: In the unmatched cohort, 73 never users and 523 ever users developed BTC, with respective incidence of 100.36 and 38.06 per 100,000 person-years. An overall risk reduction was observed in metformin users in all three regression models with respective hazard ratio (95% confidence interval) of 0.442 (0.344-0.568), 0.377 (0.295-0.481) and 0.477 (0.370-0.615). The tertile analyses showed a dose-response pattern with a neutral effect in the first tertile when metformin use was <2 years and a significant risk reduction in the second and third tertiles. Findings in the matched cohort were consistent with those observed in the unmatched cohort. The overall survival did not differ significantly between ever and never users of metformin among patients who developed BTC. Conclusions: Metformin significantly reduces the overall risk of BTC by 50%-60%. A dose-response effect is observed and users of approximately 2 years show significantly reduced risk. However, metformin does not affect the overall survival in patients with BTC.